How does general and specific human capital drive technology development in firms? - Jihoon Shin; Miguel Amaral; Ana Cristina Barros; M. Granger Morgan (PLoS ONE, 2025)
This paper examines the extent to which human capital within a firm is associated with technology development. We develop and apply an original and more objective measure of technological advancement based on companies’ transitions from their current economic activity into a new one involving a higher or lower level of technological intensity. We use data from 2009 to 2015, when CAE Rev.3 was adopted, to ensure better harmonization of the dataset. The study focuses on technology intensity within manufacturing industries, based on two-digit CAE codes. We use an extremely rich longitudinal matched employer-employee micro dataset, Quadros de Pessoal, which covers nearly all Portuguese private companies and their employees. Our results show that three factors contribute positively and significantly to technology development: education level, prior work experience in the same industry, and the combination of STEM education with prior work experience in the same industry. This paper advances understanding of the link between human capital and technology development by introducing an objective measure of technological advancement, adopting a conceptual framework that emphasizes the combined effects of human capital, and demonstrating the value of matched employer-employee microdata for analyzing firms’ technological trajectories. The findings also provide managerial and policy insights into how to increase the likelihood and speed of technology development.